2023
DOI: 10.14245/ns.2346070.035
|View full text |Cite
|
Sign up to set email alerts
|

Floor-Mounted Robotic Pedicle Screw Placement in Lumbar Spine Surgery: An Analysis of 1,050 Screws

Abstract: Objective: To analyze the usage of floor-mounted robot in minimally invasive lumbar fusion.Methods: Patients who underwent minimally invasive lumbar fusion for degenerative pathology using floor-mounted robot (ExcelsiusGPS) were included. Pedicle screw accuracy, proximal level violation rate, pedicle screw size, screw-related complications, and robot abandonment rate were analyzed.Results: Two hundred twenty-nine patients were included. Most surgeries were primary single-level fusion. Sixty-five percent of sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Even with the limitations associated with stand-alone robotic assistance, studies have reported favorable results regarding the accuracy of pedicle screw insertions in the range of 94.5% and 99% [37,40,[50][51][52]. One study investigating floormounted robotic pedicle screw placement found pedicle screw accuracy in 229 patients with 1050 screws to be 96.4% [53]. As software programs and available technology continue to advance, surgeons will adapt.…”
Section: Advanced Systems and Clinical Resultsmentioning
confidence: 99%
“…Even with the limitations associated with stand-alone robotic assistance, studies have reported favorable results regarding the accuracy of pedicle screw insertions in the range of 94.5% and 99% [37,40,[50][51][52]. One study investigating floormounted robotic pedicle screw placement found pedicle screw accuracy in 229 patients with 1050 screws to be 96.4% [53]. As software programs and available technology continue to advance, surgeons will adapt.…”
Section: Advanced Systems and Clinical Resultsmentioning
confidence: 99%
“…One notable advancement in this area is the utilization of robot-assisted (RA) techniques in spinal surgery, which provide enhanced safety, accuracy, and minimal invasion compared to conventional surgical techniques. 1 Shahi et al 2 investigated the application of floor-mounted robot (ExcelsiusGPS, Globus Medical, Inc., Audubon, PA, USA) in minimally invasive lumbar fusion. They included a large sample size of 229 patients with 1,050 pedicle screws, and found that the accuracy of pedicle screw placement in RA methods was 96.4%, and the proximal facet and proximal endplate violation rates were 0.4% and 0.9%, respectively, indicating that RA techniques contributed to excellent accuracy, large screw size, and negligible screw-related complications.…”
mentioning
confidence: 99%